Lake dynamics: observation and high-resolution numerical simulation - Rohden, Christoph von; Ilmberger, Johann; Wittum, Gabriel; Roth, Kurt (Reactive flows, diffusion and transport, 2007)
We have demonstrated the rich set of hydrodynamic phenomena that operate in a natural lake. State-of-the-art experimental methods yeild a wealth of data that are highly resolved in time and in one space axis. The orthogonal space is sampled only very sparsely, however. Still, such data allow the estimation of crucial effective parameters like vertical diffusion coefficients. Numerical simulations, on the other hand, yeild high resoution results for theentire space. They are thus inherently more powerful than experimental observations and heuristic analysis whenever a complicated to pography is crucial. However, even with the current most advanced slovers, such high-resolution studies of most phenomena on realistic time scales is beyond reach. Confining experiemntal and numerical approaches hence appears as the optimal way to reach a deeper understanding of the lake hydrodynamics.